Influência do monitoramento pelos cotistas na performance e captação dos fundos brasileiros de investimento em ações - Renato Alfredo Lazo Paz (2016)
One of the potential problems in professional portfolio management is the existence of the principal-agent problem. In the case of the investment fund industry, the agent is the manager and / or administrator and the conflict arises from the possibility that they adopt strategies or carry out activities to achieve their own interests to the detriment investors interests. The existence of this problem entails costs, called agency costs, which could adversely affect the funds performance. Therefore, in principle, activities that the investor can carry on in order to reduce the negative effects of this problem could positively influence the performance of their investments. These activities are called monitoring. In this context, the aim of this research was to analyze the effect of investor monitoring on performance and flow of funds of equityinvestment funds in the Brazilian market. The period selected for the study was from january 2005 to april 2015. The categories of equity funds analyzed were: dividends, Ibovespa active, Ibrx active, small caps, sustainability/governance and equity free. Once collected the informationof the funds, the sample was splitted into two subsamples: retail and institutional funds. This arrangement corresponds to the clientele to which the funds are allocated. The purpose of this analysis was to compare the performance and the flow of funds of two clienteles with expected different capabilities. In addition to the descriptive analysis (comparison between samples) three econometric models were estimated that related the performance of the funds - measured byJensens Alpha and Generalized Sharpe Ratio (GSR) - and the net fund inflows, with a set of investor monitoring proxy variables. The proxy variables used were: type of investors, minimum initial investment value (VMAI), type of fund manager, funds relationship with a commercialbank and the adherence of the fund to the Anbimas regulation and best practices seal. The strongest evidence in favor of the effects of investor monitoring was found in the sample of retail funds, since the proxy variables type of fund manager and VMAI were statistically significant.In addition, evidence of the negative effects of the management and performance fees were stronger in that sample, when the fund performance was measured by Jensens Alpha. In the case of institutional fund, and their sub-samples, the results were not the same, which could point the existence of distinctions that could be attributed to differences in investor monitoring capabilities. Regarding the net fund inflow, it was possible to identify evidence of increasing sophistication of institutional investors compared to retail investors, which indicate differences in each investor profile, as showed in previous studies. However, the proxy monitoring variables were not statistically significant. The main contribution of this study was to present empirical evidencethat would indicate the existance of a better performance of institutional funds compared to retail funds, which was significant when controlling for variables commonly used in the literature. The results would add evidence consistent with the principle that a greater ability to monitorthe fund managers behavior would have positive effects on the investment fund performance. However, this ability is not the same in all clienteles, which can be observed when analyzing the net fund inflows.